An Evidence-Based Medical Review on Preoperative Exercise Prehabilitation in Lung Cancer Patients - Zhang R; Wu M; Cheng Y; Xu Y; Xia L (Journal of Multidisciplinary Healthcare)
Rui Zhang,1– 3,* Mei Wu,4,* Yun Cheng,2 Yamin Xu,5 Lu Xia4 1Faculty of Military Health Services, Naval Medical University, Shanghai, 200438, People’s Republic of China; 2Department of Nursing, Huadong Hospital Affiliated to Fudan University, Shanghai, 200040, People’s Republic of China; 3School of Nursing, Fudan University, Shanghai, 200030, People’s Republic of China; 4Day Surgery Unit, Huadong Hospital Affiliated to Fudan University, Shanghai, 200040, People’s Republic of China; 5Day Chemotherapy Ward, Huadong Hospital Affiliated to Fudan University, Shanghai, 200040, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yamin Xu, Day Chemotherapy Ward, Huadong Hospital Affiliated to Fudan University, No. 221 of Yanan West Road, Jingan District, Shanghai, 200040, People’s Republic of China, Tel +86 21-62483180-530402, Email yamin_x@163.com Lu Xia, Day Surgery Unit, Huadong Hospital Affiliated to Fudan University, No. 221 of Yanan West Road, Jingan District, Shanghai, 200040, People’s Republic of China, Tel +86 21-62483180-530401, Email yihaibeilu@126.comObjective: Preoperative exercise prehabilitation in lung cancer patients can improve preoperative functional reserve, reduce postoperative complications, accelerate postoperative recovery compared with postoperative rehabilitation. To integrate and evaluate the evidence related to preoperative exercise prehabilitation in patients with lung cancer.Methods: Conducted utilizing the “ 6S” model of evidence resources, according to the search strategy searching for relevant guidelines, evidence summaries, best practices, systematic reviews, and expert consensuses on preoperative exercise prehabilitation for lung cancer patients. Based on the evidence inclusion and exclusion criteria, filter out relevant literature published between the beginning of each database and December 2024. Evaluated the quality of the selected literature, and then synthesis the evidence from the literature and made the recommendation level formulation.Results: There were 16 pieces of literature in total, including two guidelines, three evidence summaries, one expert consensus, and ten systematic reviews. Twenty-two pieces of evidence were summarized from seven aspects: patient selection and assessment, exercise implementation and supervision, type of the exercise program, exercise prescription, safety of the exercise program, adherence to exercise program and exercise outcome evaluation.Conclusion: The evidence presented in this study is scientific, comprehensive and of good clinical applicability, which can provide an evidence-based basis for medical staff to carry out preoperative exercise prehabilitation of lung cancer patients.Keywords: lung neoplasms, prehabilitation, preoperative exercise, evidence summary, evidence-based nursing